Crystal structure and low-temperature magnetic properties of R2Au2Pb (R = Y, La–Nd, Sm, Gd–Lu) plumbides - Gulay, Lubomir; Kaczorowski, Dariusz (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2023)
Polycrystalline samples of the ternary compounds R2Au2Pb (R = Y, La, Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu) were studied by means of powder X-ray diffraction and magnetic measurements. All these materials were found to crystallize with a tetragonal crystal structure of the Er2Au2Sn type (space group P42/mnm, Pearson code tP20). The Y-, La-, and Lu-based phases were established to be diamagnetic, while Yb2Au2Pb was characterized as an intermediate valence system due to an unstable 4f shell. All the other R2Au2Pb ternaries were found to order antiferromagnetically at low temperatures (TN in the range 2–30 K) due to the localized magnetic moments carried on trivalent R3+ ions.